2019
DOI: 10.1039/c9ra03170g
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped fluorescent carbon dots used for the imaging and tracing of different cancer cells

Abstract: Here, we report the synthesis of nitrogen-doped fluorescent carbon (C) dots using a one-pot hydrothermal method. Transmission electron microscopy results reveal that the particle size of the nitrogen-doped Cdots is very small, with an average diameter of 4.6 nm. After being kept in water for 10 days, the nitrogen-doped C-dots can still dissolve well in the water, showing good stability and compatibility in aqueous solution. The fluorescence spectra show that the nitrogen-doped C-dots exhibit emissiontunable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Female mice (3-4 weeks of age) were implanted with fibrosarcoma cancer cells by subcutaneous injection. The mice were separated randomly into two groups as a control and treatment group (n = 8) for in vivo therapy experiments when the tumor volume appeared to be about 25-100 mm 3 . For in vivo chemotherapy study, the control group (Saline, 200 μL) and treatment group (Chalcone-APBA-CDs, 200 μL, 0.2 mg/mL -1 ) were intraperitoneally injected every two days for 31 days.…”
Section: Tumor Model and In Vivo Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Female mice (3-4 weeks of age) were implanted with fibrosarcoma cancer cells by subcutaneous injection. The mice were separated randomly into two groups as a control and treatment group (n = 8) for in vivo therapy experiments when the tumor volume appeared to be about 25-100 mm 3 . For in vivo chemotherapy study, the control group (Saline, 200 μL) and treatment group (Chalcone-APBA-CDs, 200 μL, 0.2 mg/mL -1 ) were intraperitoneally injected every two days for 31 days.…”
Section: Tumor Model and In Vivo Chemotherapymentioning
confidence: 99%
“…However, most of this therapy has many damaging side effects, which led to various other derivate diseases 2 . Therefore, many efforts have been made to avoid the use of therapy by using advanced nanotechnology 3 . Generally, fluorescent imaging and drug delivery systems using nanoparticles have been developed with various drug-free pharmacological properties and reduced toxic side effects 4 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, drug nanocarriers were reported to have improved cancer treatment efficacy and diminish side effects of the conventional methods [30][31]. Several studies have reported the application of CNDs on cancer treatment [32][33][34]. In the present study, we synthesized potential carbon nanodots (CNDs) from catechin as a natural product isolated from Uncaria gambir.…”
Section: ■ Introductionmentioning
confidence: 97%